Transcriptomic and Metabolomic Profiling in Helicobacter pylori–Induced Gastric Cancer Identified Prognosis- and Immunotherapy-Relevant Gene Signatures - Liu, Duanrui; Zhu, Jingyu; Ma, Xiaoli; Zhang, Lulu; Wu, Yufei; Zhu, Wenshuai; Xing, Yuanxin; Jia, Yanfei; Wang, Yunshan (Frontiers in Cell and Developmental Biology, 2021)
Background. Chronic Helicobacter pylori (HP) infection is considered the major cause of non-cardia gastric cancer. However, how HP infection influence on metabolism and further regulate the progression of GC remain largely unknown. Methods. We comprehensively evaluated the metabolic pattern of HP-positive (HP+) GC samples using transcriptomic data, and correlated these patterns with the tumor microenvironment (TME)-infiltrating characteristics. The metabolic score was constructed to quantify metabolic patterns of individual tumors using principal component analysis (PCA) algorithms. The expression alternation of key metabolism-related genes (MRGs) and the downstream metabolites was validated by PCR and untargeted metabolomics analysis. Results. Two distinct metabolic patterns and differential metabolic scores were determined in HP+ GC, which were commonly associated with different clinical outcomes and biological pathways. The TME-infiltrating characteristics under these two patterns were highly consistent with the immune phenotypes. Further analysis indicated that low metabolic sore was correlated with increased EMT subtype, immunosuppression status and poorer survival. Importantly, we identified that the expression of five MRGs, including GSS, GMPPA, OGDH, SGPP2 and PIK3CA, was remarkably correlated with HP infection, patients’ survival and therapy response. Furthermore, carbohydrate metabolism and citric acid may be a downstream regulator of the function of metabolic genes in HP-induced GC. Conclusions. Our findings suggest that it’s a crosstalk of metabolism and immune promotion during HP infection. Specific transcriptional alterations in metabolic genes may act as predictive biomarkers of survival outcome and potential targets for novel therapeutic intervention in HP-induced GC patients. Key words: Helicobacter pylori, gastric cancer, cancer metabolism, tumor environment, prognosis.